Functions of Bounded κφ-Variation in the Sense of Riesz-Korenblum - Mariela Castillo; Sergio Rivas; María Sanoja; Iván Zea (Journal of Function Spaces and Applications)
We present the space of functions of bounded κφ-variation in the sense of Riesz-Korenblum, denoted by κBVφ[a,b], which is a combination of the notions of bounded φ-variation in the sense of Riesz and bounded κ-variation in the sense of Korenblum. Moreover, we prove that the space generated by this class of functions is a Banach space with a given norm and we prove that the uniformly bounded composition operator satisfies Matkowski's weak condition.